The future of experiential learning within the department of engineering at Reykjavík University - Hafrún Helga Haraldsdóttir 1991- (2020)
In this study, it was analysed how the department of engineering at Reykjavík University is using experiential learning today and answer provided to the question if experiential learning should be considered to be used more. Qualitative method approach was used where the current situation at Reykjavík University was evaluated with semi-structured interviews, and from that, opportunities in the environment around the university were explored with experiential learning in mind. The results indicate that experiential learning should be used more and ideas for activities in the university environment are introduced with a time plan and cost estimate. Í þessari ritgerð var skoðað hvernig verkfræðideildin innan Háskólans í Reykjavík er að nota reynslunám í dag og spurningunni um hvort það ætti að vera meira notað er svarað. Eigindleg rannsóknaraðferð var notuð þar sem núverandi staða á notkun reynslunáms innan Háskólans í Reykjavík var metin með hálfstöðluðum viðtölum og út frá því voru tækifæri í umhverfinu í kringum háskólann skoðuð með reynslunám í huga. Niðurstöðurnar gefa til kynna að reynslunám ætti að vera notað meira og hugmyndir fyrir æfingar og verkefni í umhverfi háskólans eru kynntar, ásamt tíma- og kostnaðaráætlun.